5PSQ-218 Haemorrhagic transformation after mechanical thrombectomy ischaemic stroke management: overview of medical device vigilance declarations. (14th March 2021) - Arquevaux, R; Polo, C; Nisse, YE; Jacob, C; Jolly, C; Demore, B
Abstract : Background and importance: There are two techniques for ischaemic stroke (IS) management: intravenous thrombolysis (IVT) and mechanical thrombectomy (MT). Haemorrhagic transformation (HT) is a complication occurring in 30–40% of patients. A pharmacovigilance (PV) and/or medical device vigilance (MDV) report should be done if this side effect potentially involves drugs or medical devices. Aim and objectives: To assess the percentage of HT after IS management with MT; to evaluate declarations of MDV following HT post-MT; and to draw a flowchart to help healthcare professionals better report side effects after IS management. Material and methods: A retrospective study was done from May to July 2020 involving patients with MT after IS. Demographic data, clinical data and management techniques were collected. Then, a flowchart was drawn with Microsoft Visio software. Results: Over the study period, 31 patients were included (sex ratio 1.07, mean age 68±10 years and mean BMI 25±4.42 kg/m 2 ). 29/31 patients had at least one risk factor to present a HT post-MT. The percentage of HT post-MT was about 39% (12/31): 5 HT post-MT only and 7 HT post-MT+IVT. All of these patients had at least one risk factor for HT. 4/5 HT post-MT only were reported in PV and 0 in MDV, and 3/7 HT post-MT+IVT were reported in PV and 0 in MDV. According to French law, 12 patients should have been reported in MDV and 5 in PV. The four patients who received MT only should not have been reported in PV because no drug was involved in the occurrence of the side effect. A flowchart to allow better reporting has been developed. Conclusion and relevance: The percentage of HT post-MT was similar to that in the literature. HT is difficult to assess and may be the result of IVT or MT, the natural history of stroke or influenced by risk factors. The number of reports done in MDV and PV after IS management post-HT was identified. There was a low rate of reports of side effects and some were reported to the wrong vigilance scheme. A flowchart was drawn to guide declarants. It will be validated and distributed in the hospital. References and/or acknowledgements: Conflict of interest: No conflict of interest